PENGARUH MODEL PBL BERBASIS KEARIFAN LOKAL KULINER SINGKAWANG BERBANTUAN VIDEO ANIMASI TERHADAP MOTIVASI BELAJAR SISWA SD - Wiwin Retnowati; Abd Basith (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low learning motivation of elementary school students on the digestive system and balanced nutrition material motivated this study. This study aims to examine the effect of the Problem Based Learning (PBL) model based on Singkawang's local culinary wisdom assisted by animated videos on students' learning motivation. The type of this research is quantitative with a one-group pretest-posttest design. The population was all fifth-grade students at SDN 32 Singkawang, consisting of 28 students, who were also taken as the sample using total sampling technique. Data collection techniques used a learning motivation questionnaire administered during the pretest and posttest. The instrument was a validated learning motivation questionnaire with 10 items. Data analysis techniques used paired sample t-test and effect size (Cohen's d). The results showed an increase in the mean motivation score from 22.4 (pretest) to 34.1 (posttest). The paired sample t-test yielded t = 24.17 (df = 27, p < 0.001), indicating a statistically significant improvement. The effect size (Cohen's d) was 4.57 (very large category). In conclusion, the PBL model based on Singkawang's local culinary wisdom with animated video assistance has a positive and significant effect on elementary school students' learning motivation. The implication of this study is that the model can serve as an innovative alternative for elementary school teachers to enhance learning motivation through local cultural contexts, as well as a reference for developing local content curricula based on cultural wisdom.